Advantages of MesoRex shunt compared with distal splenorenal shunt for extrahepatic portal vein occlusion in children - Khamag, Omer (Division of Paediatric Surgery, 2023)
Background: Portal hypertension (PH) is a common complication of chronic liver or portal vein pathology in children. It is defined as a pathological increase in the pressure of the portal venous system. There are two leading causes for PH in children, pre and post sinusoidal liver disease and pre-hepatic non-cirrhotic portal vein obstruction, also referred to as extrahepatic portal vein obstruction (EHPVO). Management of EHPVO is primarily surgical, with surgical portosystemic shunting representing a safe and effective method for the long-term management of portal hypertension in the paediatric population. Although different shunts have been proposed for EHPVO, both the MesoRex shunt and distal splenorenal shunt have shown the most promising results as effective and definitive approaches to alleviating EHPVO. Aim: To review surgical management of extrahepatic portal vein obstruction (EHPVO) at Red Cross War Memorial Children's Hospital (RXH) and compare MesoRex shunt (MRS) with distal splenorenal shunt (DSRS). To determine and compare the shunt success rate, defined as longterm patency at 24 months of the MesoRex shunt and distal splenorenal shunt, the factors that could have influenced the patency of the Rex vein and the effect of these procedures on the long-term synthetic liver function. Methods: This study followed a retrospective study design, conducted at a single centre documenting pre- and post-operative data in 21 children, 14 MRS and 7 DSRS, All patients presented to RCWMCH with EHPVO over an 18-year period (2001-2019) were eligible for inclusion either for MRS or DSRS. Exclusion criteria included patients lost to follow up, patients who had atypical shunts not falling into either the DSRS or MRS operation and those with insufficient or missing clinical records over 18 years. Details of patient demographics included age, gender, aetiology, preoperative symptomatology, Rex vein patency, history of neonatal umbilical vein catheterization (UVC), age at shunt surgery and shunt patency were compiled over an average follow up period of 11 years (2-18). Bloodwork analysis included albumin, prothrombin time (PT), partial thromboplastin time (PTT), International normalized ratio (INR), fibrinogen, total bilirubin, liver enzymes and platelets prior to and two-years-post shunt surgery. Rex vein patency was assessed preoperatively. Statistical significance was determined at P<0.05 following a two-tailed t-test. Results: Out of 23 patients presenting with EHPVO, two children lost follow up immediately after diagnosis and were excluded. Twenty-one patients were operated on and followed up long term, with 14 patients (66%) in the MesoRex shunt group and seven patients (33%) in the distal splenorenal shunt group. Fourteen of the 15 MesoRex procedures (93%) were deemed successful in comparison to five out of seven (71%) in the distal splenorenal shunt group. Significant improvements were seen in MesoRex shunt recipients regarding the levels of Albumin, PT, PTT, and platelets. The other liver functions measured, including INR, fibrinogen, total bilirubin, ALT, AST, GGT, and ALP, were within the normal physiological range. The distal splenorenal shunt cohort only yielded a significant improvement in the platelet count, increasing from a mean value of 100 to 149.83 (P = 0.02). Out of those who showed successful surgical intervention in the long term (14 in MRS and 5 in DSRS cohorts), only one child with MRS experienced 2 episodes of variceal bleeding despite having patent shunt with adequate flow (more than 20cm/second). However, no further surgical intervention was needed, and the bleeding resolved spontaneously. Conclusion: This study highlights that MesoRex shunt has a better long-term outcome in extra hepatic portal vein obstruction and improves liver synthetic function and must be considered as the primary definitive intervention. DSRS does control variceal bleeding due to extra hepatic portal hypertension but may have a negative effect on liver function on long term and is only considered when MRS is not technically feasible or as a salvage procedure when MRS fails.